Gender perspectives of the water, energy, land, and food security nexus in sub-Saharan Africa - Hlahla, Sithabile (Frontiers in Sustainable Food Systems, 2022)
The water, energy, land and food (WELF) nexus has been touted as a cross-sectoral systems approach that presents an opportunity to address the grand challenges related to poverty, unemployment, inequality and climate change, especially in the global South. However, as with any other developmental approach, the WELF nexus needs to mainstream gender, which often lies at the heart of poverty, unemployment, and inequality in sub-Saharan Africa. Access to water, energy, land and food is gendered, and so are livelihood strategies and climate change responses. Inequitable access to these resources, gender inequalities, socio-economic vulnerability and cultural norms contribute to women's susceptibility to the impacts of climate change and limit their ability to harness opportunities arising from it. Reducing women's vulnerability to the impacts of climate change in SSA and improving equity in natural resource access and resource use efficiencies will require transformation of gender relations and the active participation of both men and women in decision-making processes. Moreover, policies and interventions that cater to the WELF nexus need be updated to be more gender-aware and sensitive, as this will also contribute to addressing Sustainable Development Goal 5, in addition to Goals 1, 2, 6, 7, and 15.